The recruitment & selection process and general HR policies & practices of Kemiko Pharmaceuticals Ltd. - Masud, Farzina Binty (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration,2014.